Screening for trisomies by cell‐free DNA testing of maternal blood: consequences of a failed result. (25th April 2016) - Revello, R.; Sarno, L.; Ispas, A.; Akolekar, R.; Nicolaides, K. H.
ABSTRACT: Objectives: First, to report the distribution of the fetal fraction of cell‐free (cf) DNA and the rate of a failed cfDNA test result in trisomies 21, 18 and 13, by comparison with pregnancies unaffected by these trisomies, second, to examine the possible effects of maternal and fetal characteristics on the fetal fraction, and third, to consider the options for further management of pregnancies with a failed result. Methods: This was a cohort study of 10 698 singleton pregnancies undergoing screening for fetal trisomies 21, 18 and 13 by cfDNA testing at 10–14 weeks' gestation. There were 160 cases of trisomy 21, 50 of trisomy 18, 16 of trisomy 13 and 10 472 were unaffected by these trisomies. Multivariate regression analysis was used to determine significant predictors of fetal fraction and a failed cfDNA test result amongst maternal and fetal characteristics. Results: Fetal fraction decreased with increasing body mass index and maternal age, was lower in women of South Asian racial origin than in Caucasians and in assisted compared to natural conceptions. It increased with fetal crown–rump length and higher levels of serum pregnancy‐associated plasma protein‐A and free β ‐human chorionic gonadotropin. The median fetal fraction was 11.0% (interquartile range (IQR), 8.3–14.4%) in the unaffected group, 10.7% (IQR, 7.8–14.3%) in trisomy 21, 8.6% (IQR, 5.0–10.2%) in trisomy 18 and 7.0% (IQR, 6.0–9.4%) in trisomy 13. There was a failed result from cfDNA testing after first sampling in 2.9% of the unaffected group, 1.9% of trisomy 21, 8.0% of trisomy 18 and 6.3% of trisomy 13. In the cases with a failed result, 7% of women had invasive testing, mainly because of high risk from the combined test and/or presence of sonographic features suggestive of trisomies 18 and 13. All cases of trisomies were detected prenatally. Conclusions: In cases of a failed cfDNA test, the rate of trisomies 18 and 13, but not trisomy 21, is higher than in those with a successful test. In the management of such cases, the decision in favor of invasive testing should depend on the risk of prior screening and the results of detailed ultrasound examination. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from theabstract to view the translations.